EDUKASI DAN PENYULUHAN PEMBUATAN SEDIAAN EMULSIGEL ANTI ACNE DARI MINYAK BUNGA CENGKEH (Syzygium aromaticum L.) TERHADAP SISWA/I DI SMA NEGERI 1 DELI TUA - Sembiring, Pintata (INSTITUT KESEHATAN DELI HUSADA, 2024)
Acne is a skin disease where the pores are clogged, causing inflamed pus pockets due to the activity of oil glands called sebaceous glands under the skin and this activity is stimulated by increased androgen hormones. Cloves are herbal plants that contain essential oil chemicals. The chemical composition of clove leaf oil mainly consists of eugenol. Eugenol has pharmacological effects as an antibacterial, analgesic and anti-inflammatory. Emulsion is a skin barrier that has received a lot of attention because of its small particle size so that it can be thermodynamically stable and can increase drug penetration. Recent advances in nanoemulsion research have created new prospects in a number of industries, including pharmaceuticals, biotechnology, food, and cosmetics. The main objective of this counseling is to provide information related to the manufacture of emulsigel preparations as anti-acne so that students at SMA Negeri 1 Deli Tua can make and through this counseling program it is hoped that there will be an increase in understanding and skill development. Thus, students can create one Anti Acne skincare product that they need and create a healthier, safer and more sustainable environment.